2020
DOI: 10.21203/rs.2.19113/v5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ada-WHIPS: Explaining AdaBoost Classification with Applications in the Health Sciences

Abstract: Background Computer Aided Diagnostics (CAD) can support medical practitioners to make critical decisions about their patients' disease conditions. Practitioners require access to the chain of reasoning behind CAD to build trust in the CAD advice and to supplement their own expertise. Yet, CAD systems might be based on black box machine learning (ML) models and high dimensional data sources (electronic health records, MRI scans, cardiotocograms, etc). These foundations make interpretation and explanation of the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Considering that a precise classification is difficult to achieve with only one model, the combination of multiple models was used in the current study. Thus, LR and AdaBoost (a black box model widely used in computer-aided diagnosis), were chosen as the sub-models according to the classification performance of each model (45).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that a precise classification is difficult to achieve with only one model, the combination of multiple models was used in the current study. Thus, LR and AdaBoost (a black box model widely used in computer-aided diagnosis), were chosen as the sub-models according to the classification performance of each model (45).…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained by analysing the percentage of clinical adherence confirmed that almost all the rules discovered by the model are also the most accepted statements among experts. Hatwell et al (2020) proposed a novel approach to explain the AdaBoost (AB) classification algorithm, a black-box model widely used in the CAD literature. The new algorithm, named Adaptive-Weighted High Importance Path Snippets (Ada-WHIPS), has been designed to provide accurate and highly-interpretable disease detection by extracting simple and logical rules from the AB model.…”
Section: Explanation Quality Assessmentmentioning
confidence: 99%
“…[14] To further confirm the RF results, we compared the results of several supervised ML models without tuning (super vector machine, logistic regression, AdaBoost, multilayer perceptron (MLP), and linear discriminant analysis). [12,[15][16][17][18] The data were split into 2 groups, 80% for training and 20% for testing, as in our RF. Additionally, we developed a generalized linear model to predict the cohort (Chilean or North American) using R (version 4.1.1; 2021-08-10, RStudio, Boston, MA) and dplyr, mlogit, tidyr libraries.…”
Section: Unsupervised and Supervised Analysismentioning
confidence: 99%